Affecting factors on the incidence of Stunting in children aged 0 – 59 months in the working area of Amplas community health center in Medan city - Rahmadhani, Mayasari; Ayu, Mayang Sari; Damanik, Rosa Zorayatamin (PT Inovasi Pratama Internasional, 2024)
Stunting is one of the targets of the Sustainable Developments Goals in order to achieve the goals by 2030, with two indicators, including eliminating famine and malnutrition. Hence, by 2025 it has been predicted that the stunting rate will be 40% reduced. The purpose of this study was to determine the factors that affect the incidence of stunting in 0-59 months children. This is an analytic observational study with a case control approach. In this study, 20 samples were selected using the total sampling technique that are divided into two groups. This study were conducted from October to November 2022. Data collection was obtained by collecting electronic-Community Based Nutrition Registration and reporting anthropometric data on 1-5 years old children. Bivariate analysis using chi-square test and model summary. The results showed that the results of the nutrition chi-square test were obtained at the value of 0.000 < 0.05, the results of the exclusive breastfeeding chi-square test were obtained at the value of 0.001 < 0.05, the results of the early complementary feeding chi-square test were obtained at the value of 0.011 < 0.05, chi-square test result of Low Birth Weight obtained a value of 0.005 < 0.05, chi-square test result of Low Birth Weight of the value of 0.005 < 0.05, chi-square test result of exclusive breastfeeding obtained with a value of 0.005 < 0.05, chi-square test result of early complementary feeding obtained with a value of 0.005 < 0.05. 005 < 0.05, the results of the chi-square test for infectious diseases obtained the value of 0.000 < 0.05, the results of the chi-square test for immunization status obtained the value of 0.007 < 0.05, These results suggest that there is an association between infectious diseases and immunization status.